Discovery of a new diol-containing polyketide by heterologous expression of a silent biosynthetic gene cluster from Streptomyces lavendulae FRI-5. (1st February 2018) - Pait, Ivy Grace Umadhay; Kitani, Shigeru; Roslan, Farah Wahidah; Ulanova, Dana; Arai, Masayoshi; Ikeda, Haruo; Nihira, Takuya
Abstract: The genome of streptomycetes has the ability to produce many novel and potentially useful bioactive compounds, but most of which are not produced under standard laboratory cultivation conditions and are referred to as silent/cryptic secondary metabolites. Streptomyces lavendulae FRI-5 produces several types of bioactive compounds. However, this strain may also have the potential to biosynthesize more useful secondary metabolites. Here, we activated a silent biosynthetic gene cluster of an uncharacterized compound from S. lavendulae FRI-5 using heterologous expression. The engineered strain carrying the silent gene cluster produced compound 5, which was undetectable in the culture broth of S. lavendulae FRI-5. Using various spectroscopic analyses, we elucidated the chemical structure of compound 5 (named lavendiol) as a new diol-containing polyketide. The proposed assembly line of lavendiol shows a unique biosynthetic mechanism for polyketide compounds. The results of this study suggest the possibility of discovering more silent useful compounds from streptomycetes by genome mining and heterologous expression.